The concept of management by flexible goals = Koncepcja zarządzania w oparciu o elastyczne cele - Krzakiewicz, Kazimierz; Cyfert, Szymon (Zielona Góra: Faculty of Economics and Management Press)
The aim of this paper is to contribute to the debate on the directions of change of contemporary organizations and present assumptions of a management concept based on flexible goals. The paper starts with the presentation of conditions in which modern organizations operate. It is followed by the discussion of the essence of the concept of governance based on flexible goals and description of the principle of agreement about relative improvements. Finally, a model of the organization implementing the management process based on flexible goals is presented and the rules of management based on flexible goals are defined.
Keywords: elastyczność organizacji; proces zarządzania; cele strategiczne; flexibility of the organization; process management; strategic objectives